Effect of Audio Visual ROM Education on Family Attitude and Motivation in Post-Stroke Care - Ixora; Dewi Wulandari (Poltekkes Kemenkes Malang, Campus III Blitar, 2025)
Stroke is a major cardiovascular disease globally, contributing significantly to mortality and disability, with an incidence rate of 12.1 cases per 1,000 population in Indonesia in 2018. Family support is crucial during the rehabilitation phase, but inadequate information often leads to incomplete family knowledge regarding disease management. Objective: This study aimed to analyze the effect of Audio Visual Education (AVE) about Range of Motion (ROM) training on the attitude and motivation of family caregivers in performing home ROM exercises for post-stroke patients. Methods: This research employed a Quasi-Experimental Design using a one-group pre-test post-test model, with a sample of 30 family caregivers selected through purposive sampling. The intervention delivered was AVE focused on ROM techniques, the Wilcoxon Sign Rank Test was used to compare pre- and post-test scores. Results: The findings demonstrated a significant positive effect on both family attitude (P-Value = 0.001) and motivation (P-Value = 0.000). The proportion of negative attitudes decreased from 63.3% to 0.0% post-intervention, while strong motivation increased dramatically from 26.7% to 93.3% after the intervention. Conclusion: Audio Visual Education on ROM exercises is highly effective in significantly improving the attitude and motivation of family caregivers in post-stroke patient care